Changing the subject: a theory of rhetorical empathy - Blankenship, Lisa, author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Explores ways of engaging across difference by studying the concept of empathy from a rhetorical perspective. Considers how empathy can be deliberate, conscious choice to understand others through listening and exploration of pathos. How language and symbol systems play in this process that is cognitive and affective.--Provided by publisher.
A brief history of empathy -- Threads of feminist rhetorical practices -- Rhetorical empathy in the gay rights-religious divide -- Beyond "common ground.".
Keywords: Empathy; Rhetoric